ANALISA TATA RUANG PARKIR DAN MANUVER KENDARAAN BERAT ANGKUTAN BARANG PADA JEMBATAN TIMBANG BERDASARKAN PERATURAN PEMERINTAH NOMOR 74 TAHUN 2014 - Arifin Dian Wardhanto; Ilham Chandra Feriawan; Djoko Purwanto; Kami Hari Basuki (Jurnal Karya Teknik Sipil, 2016)
Weighbridge is one of facilities used to control the freight transport in Indonesia. This study aims to determine the proper parking configuration that can be applied to every weighbridges in Indonesia, to support The Government Regulation Number 74, 2014. This study uses Tanjung Weighbridge and Toyoga Weighbridge as the location of the focus case. In this study, the main thing to be analyzed are the parking space requirement and the requirement of space for vehicles’ movements. The method used to analyze the parking space requirement is the calculation method by using the load inspection data provided by Dishubkominfo Jateng. Whilst the method used to analyze the requirement of space for vehicles’ movement is the simulation method, by using Vehicle Tracking software. The result is obtained from the calculations of the parking space requirement, with the result of 3 parking spaces for Medium Truck, 4 parking spaces for Big Truck, and 2 parking spaces for Coupled Truck and Semitrailer at Tanjung Weighbridge. For Toyoga Weighbridges, the required parking spaces are 2 parking spaces for Medium Truck, 4 parking spaces for Big Truck, and 3 parking spaces for Coupled Truck and Semitrailer. The result of the parking layout configuration concludes that those weighbridges don’t have enough available space to accommodate the amount of the required parking spaces, so the area of those weighbridges need expansion, with the land expansion of 1576 m2 for Tanjung Weighbridge and 1682 m2 for Toyoga Weighbridge. After that, by using the result of parking configuration for those two weighbridges, the ideal parking configuration can be configured as the base of parking configuration for every weighbridges in Indonesia. Based on the analysis that we did, Tanjung and Toyoga Weighbridges need area expansion to provide a good parking configuration and also need to improve the infrastructure and human resources in order to support the ability of those weighbridges to match the new government regulation.